2011
DOI: 10.1007/s10334-011-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air susceptibility on proton resonance frequency MR thermometry

Abstract: Air susceptibility changes associated with oxygen concentration changes greatly affect PRF MR thermometry measurements. Air temperature changes can also affect these measurements, but to a smaller degree. For uncalibrated MR thermometry, air susceptibility changes may be a significant source of error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…As an example, the severe over-and underestimation of PRF readings due to perfusion changes in muscle and tumour tissue is demonstrated in Figure 1b. In general alterations in the concentration of oxygen, which in its pure form is paramagnetic and diamagnetic when bound to hemoglobin (oxyhemoglobin) affect the local static magnetic field (49,68). The direction of perfusion influences these local field changes (69).…”
Section: Perfusionmentioning
confidence: 99%
“…As an example, the severe over-and underestimation of PRF readings due to perfusion changes in muscle and tumour tissue is demonstrated in Figure 1b. In general alterations in the concentration of oxygen, which in its pure form is paramagnetic and diamagnetic when bound to hemoglobin (oxyhemoglobin) affect the local static magnetic field (49,68). The direction of perfusion influences these local field changes (69).…”
Section: Perfusionmentioning
confidence: 99%
“…These include a) drift in the static field [146], b) patient motion [16,63,147], c) local or global changes in magnetic susceptibility (e.g. due to tissue swelling [148], fat [46,161] air [149], movement of interstitial applicators [43] or injection of contrast agent [150]), which can be altered by heating itself [49]. For example, although the screening constant of fat is not temperature-dependent, its susceptibility is, and so is the susceptibility of every other tissue, thus introducing weak tissue-type dependence.…”
Section: Limitations In Methods Based On the Chemical Shift Of Water mentioning
confidence: 99%
“…They may arise from organ movement [6,7], tissue susceptibility changes due to freezing [8] or fat susceptibility change due to the temperature changes [9]. They may even be caused by susceptibility changes in surrounding air [10].…”
Section: Contentsmentioning
confidence: 99%
“…Streicher et al [10] showed in measurements and simulations that air susceptibility change with temperature has a measurable effect on uncorrected MR thermometry and an even stronger effect when oxygen concentration is changed. This effect can lead to PRF temperature errors of up to 40 K.…”
Section: Contentsmentioning
confidence: 99%